Controlling Sulfuryl-Transfer Biology. Issue 5 (19th May 2016) - Cook, Ian; Wang, Ting; Wang, Wei; Kopp, Felix; Wu, Peng; Leyh, Thomas S.
Summary: In humans, the cytosolic sulfotransferases (SULTs) catalyze regiospecific transfer of the sulfuryl moiety (–SO3 ) from 3′-phosphoadenosine 5′-phosphosulfate to thousands of metabolites, including numerous signaling small molecules, and thus regulates their activities and half-lives. Imbalances in the in vivo set points of these reactions leads to disease. Here, with the goal of controlling sulfonation in vivo, molecular ligand-recognition principles in the SULT and nuclear receptor families are integrated in creating a strategy that can prevent sulfonation of a compound without significantly altering its receptor affinity, or inhibiting SULTS. The strategy is validated by using it to control the sulfonation and estrogen receptor (ER) activating activity of raloxifene (a US Food and Drug Administration-approved selective estrogen receptor modulator) and its derivatives. Preventing sulfonation is shown to enhance ER-activation efficacy 10 4 -fold in studies using Ishikawa cells. The strategy offers the opportunity to control sulfuryl transfer on a compound-by-compound basis, to enhance the efficacy of sulfonated drugs, and to explore the biology of sulfuryl transfer with unprecedented precision. Graphical Abstract: Highlights: Sulfuryl transfer broadly regulates small-molecule signaling A strategy for controlling small-molecule sulfonation in vivo is presented The strategy does not inhibit SULTs or significantly alter receptor binding The strategy can be used to enhance therapeutics and probe sulfur metabolism Abstract : Cook et al. have developed a molecular-design strategy that can control the sulfonation of individual signaling small molecules without inhibiting SULTs, which catalyze sulfonation, or significantly altering their receptor affinities. Sulfonation determines the bioactivities and terminal half-lives of hundreds of human signaling molecules.